Meningkatkan Pengetahuan Pengelolaan Informasi Perpustakaan Sekolah Pada Siswa Sekolah Dasar di Wilayah Klabang, Jatirejo, Sawit dan Boyolali - Carlos Rionard Ransom (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Elementary school is a place of learning to receive basic education. Learning is a process of behavior change achieved through human experience. This service aims to expand knowledge about the application of book management in life to support student learning at Klavan State Elementary School. The method used is based on student advice and practical training. This activity begins by asking students to organize their books, catalog their books, and arrange their books on traditional shelves. After that, we continued to provide guidance and practice on inputting book data and displaying report results when utilizing electronic information management in school libraries. After this activity, it is hoped that elementary school students in Klabang province will be influenced to implement book arrangements in their respective homes to help students effectively and efficiently find personal books to use in learning, as well as gain additional knowledge.